Binder and preparation method thereof, diaphragm, battery and electric equipment
By adopting a core-shell structure adhesive, using the combination of organic polymer adhesive and phosphate inorganic adhesive, the problem of insufficient performance in the breathability and thermal stability of the existing ceramic-coated diaphragm adhesive is solved, and the high thermal stability and low impedance effect of the diaphragm are achieved.
Patent Information
- Application Number
- CN202411218693.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-04-11
AI Technical Summary
The existing ceramic coated separator adhesives have insufficient performance in terms of breathability, thermal stability, etc., making it difficult to meet the requirements of mid-to-high-end lithium-ion batteries.
The adhesive with a core-shell structure is adopted. The core is an organic polymer binder and the shell is a phosphate inorganic binder. The aluminum hydroxide coating layer is formed through emulsion polymerization reaction and aluminum source reaction, and then reacts with phosphoric acid to form a phosphate inorganic binder coating layer.
The thermal stability and breathability of the diaphragm are improved, the swelling of the binder is reduced, and the diaphragm remains stable under high temperature and electrolyte immersion conditions, reducing the diaphragm impedance.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to an adhesive and a preparation method thereof, a diaphragm, a battery and electrical equipment. Background Art
[0002] As a green, environmentally friendly and pollution-free secondary battery, the application field of lithium batteries has expanded from the initial small digital electronic products to new energy fields such as electric vehicles and energy storage power stations for large-scale energy storage technologies. Battery separators are the core materials that affect the quality and safety performance of lithium-ion batteries. At present, the commercialization of lithium-ion battery separators is mainly polyolefin materials, such as polyethylene (PE) and polypropylene (PP), which are used to provide ion channels and isolate electronic conduction to avoid short circuits between positive and negative electrodes due to direct contact. Therefore, the separator plays a very important role in the charging and discharging characteristics and safety performance of the battery. However, the separator is prone to shrinkage at high temperatures, resulting in short circuits between the positive and negative electrodes. At the same time, the low surface energy of PE and PP makes them poorly wettable to the electrolyte. In order to improve the thermal shrinkage performance of the separator and improve the temperature resistance of the separator, the current common method is to form a ceramic coating by ceramic coating on the surface of the separator.
[0003] Ceramic coating diaphragm is a new generation of diaphragm used in mid-to-high-end lithium-ion batteries. Its core material is coating adhesive. Existing products fail to fully meet the requirements of ceramic coating diaphragm adhesive for various performance aspects such as air permeability and thermal stability. Summary of the invention
[0004] In view of the problems existing in the prior art, the present application provides a binder and a preparation method thereof, a diaphragm, a battery and an electrical device.
[0005] In order to solve the above problems, this application provides the following solutions.
[0006] In a first aspect, the present application provides a binder having a core-shell structure, wherein the core of the core-shell structure comprises an organic polymer binder; and the shell of the core-shell structure comprises a phosphate inorganic binder.
[0007] In some embodiments, the organic polymer binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-chlorotrifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trifluoroethylene copolymer, and polyvinylidene fluoride-chlorofluoroethylene copolymer; the phosphate inorganic binder includes at least one of aluminum phosphate and aluminum dihydrogen phosphate.
[0008] In some embodiments, the average particle size of the binder is 0.2 μm to 8 μm.
[0009] In a second aspect, the present application provides a method for preparing a binder, comprising the following steps:
[0010] S1: adding a nonionic surfactant to a solution containing the organic polymer binder to obtain a mixed emulsion;
[0011] S2: adding an aluminum source to the mixed emulsion for reaction, and drying to obtain an organic polymer binder coated with aluminum hydroxide;
[0012] S3: mixing the aluminum hydroxide coated organic polymer binder and phosphoric acid for reaction, and drying to obtain the phosphate inorganic binder coated organic polymer binder.
[0013] In some embodiments, step S1 further includes adding alkanes, fatty alcohols and deionized water to the mixed emulsion.
[0014] In some embodiments, the weight ratio of the alkane, the fatty alcohol, the nonionic surfactant, and the deionized water is (7-11):1:1:(10-30).
[0015] In some embodiments, in step S1, the alkane includes an alkane having 5 to 10 carbon atoms; and / or the fatty alcohol includes a fatty alcohol having 5 to 10 carbon atoms.
[0016] In some embodiments, the nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether AEO-9, fatty alcohol polyoxyethylene ether AEO-7, fatty alcohol polyoxyethylene ether AEO-15, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer P123, linear secondary alcohol polyoxyethylene ether Tergitol 15-S-9, fatty alcohol polyoxyethylene ether Genapol X-080 and nonylphenol polyoxyethylene ether TX-10.
[0017] In some embodiments, the alkane comprises at least one of n-octane, n-pentane, n-hexane, n-heptane, 2-methylpentane, 3-methylhexane, cyclopentane, cyclohexane and isooctane; and / or the fatty alcohol comprises at least one of ethanol, n-octanol and n-butanol.
[0018] In some embodiments, the aluminum source includes at least one of sodium metaaluminate, aluminum isopropoxide, and aluminum nitrate.
[0019] In some embodiments, in step S2, the weight ratio of the mixed emulsion to the aluminum source is 1:(0.1-1.1).
[0020] In some embodiments, in step S3, the weight ratio of the organic polymer binder coated with aluminum hydroxide to the phosphoric acid is 1:(2-4).
[0021] In a third aspect, the present application provides a diaphragm, comprising a base film and a coating arranged on the surface of at least one side of the base film, wherein the coating comprises an adhesive as described in any one of the first aspects or an adhesive prepared by the method for preparing the adhesive as described in any one of the second aspects.
[0022] In some embodiments, the coating includes ceramic particles, and the weight ratio of the binder to the ceramic particles is (0.3-1):(99-99.7).
[0023] In some embodiments, the average particle size of the ceramic particles is 100 nm to 500 nm; and / or the ceramic particles include one or more of boehmite, aluminum oxide, barium titanate, zirconium oxide, and magnesium hydroxide.
[0024] In some embodiments, the coating includes a wetting agent.
[0025] In some embodiments, the coating has a thickness of 0.3 μm to 3 μm; and / or the coating has an air permeability per unit thickness of less than 30 s 100 cc -1 μm -1 .
[0026] In a fourth aspect, the present application provides a battery, comprising the separator described in any one of the third aspects.
[0027] In a fifth aspect, the present application provides an electrical device comprising the battery described in the fourth aspect.
[0028] The binder provided in the present application has the following effects: the binder described in the present application is used in the diaphragm coating, the binder is a core-shell structure, with an organic polymer binder as the core and a phosphate inorganic binder as the shell, the phosphate inorganic binder has high thermal stability and will not expand in the electrolyte, reducing the swelling of the binder, so that the diaphragm remains stable at a relatively high temperature and when immersed in the electrolyte; coating the organic polymer binder with the phosphate inorganic binder can reduce the amount of organic polymer binder used, which is beneficial to reducing the impedance of the diaphragm and increasing the air permeability of the diaphragm. DETAILED DESCRIPTION
[0029] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] The invention provides a binder, which is a core-shell structure, wherein the core of the core-shell structure comprises an organic polymer binder, and the shell of the core-shell structure comprises a phosphate inorganic binder.
[0031] Specifically, the organic polymer binder is formed by emulsion polymerization. The polymer binder formed by emulsion polymerization has a wide molecular weight distribution, a small particle size (0.2μm-8μm), a high degree of crystallinity, a high melting point, and low swelling. When applied to the diaphragm coating, it is beneficial to reduce the coating thickness and reduce the overall impedance of the diaphragm; the organic polymer binder achieves firm bonding of materials through physical and chemical effects between polymer molecules; the phosphate inorganic binder has a variety of preparation methods, has good bonding properties, high temperature resistance, corrosion resistance, does not contain harmful substances, is environmentally friendly and pollution-free, and has excellent application prospects.
[0032] The binder provided in the present application has the following effects: the binder described in the present application is used in the diaphragm coating, the binder is a core-shell structure, with an organic polymer binder as the core and a phosphate inorganic binder as the shell, the phosphate inorganic binder has high thermal stability and will not expand in the electrolyte, reducing the swelling of the binder, so that the diaphragm remains stable at a relatively high temperature and when immersed in the electrolyte; coating the organic polymer binder with the phosphate inorganic binder can reduce the amount of organic polymer binder used, which is beneficial to reducing the impedance of the diaphragm and increasing the air permeability of the diaphragm.
[0033] In some embodiments, the organic polymer binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-chlorotrifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trifluoroethylene copolymer and polyvinylidene fluoride-chlorofluoroethylene copolymer; the phosphate inorganic binder includes at least one of aluminum phosphate and aluminum dihydrogen phosphate.
[0034] Specifically, the above-mentioned organic polymer binder and phosphate inorganic binder have excellent bonding strength and stability, and the preparation method is simple and the industrialization degree is high.
[0035] In some embodiments, the phosphate inorganic binder may further include magnesium phosphate and chromium phosphate.
[0036] In some preferred embodiments, the organic polymer binder includes polyvinylidene fluoride; and the phosphate inorganic binder includes aluminum dihydrogen phosphate.
[0037] In some embodiments, the average particle size of the binder is 0.2 μm to 8 μm.
[0038] Specifically, the particle size of the binder can be, but is not limited to, 0.2 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, and 8 μm. The average particle size of the binder is the statistical average of the particle size in the material, which can be measured and analyzed by laser diffraction particle size analysis, electron microscope image analysis, etc. The larger the particle size of the binder, the stronger the bonding ability of the binder, and the smaller the particle size of the binder, the smaller the internal resistance of the diaphragm, which is beneficial to improving the conductivity of the battery.
[0039] In a second aspect, the present application provides a method for preparing the above-mentioned binder, comprising the following steps:
[0040] S1: adding a nonionic surfactant to a solution containing an organic polymer binder to obtain a mixed emulsion;
[0041] S2: adding an aluminum source to the mixed emulsion for reaction, and drying to obtain an organic polymer binder coated with aluminum hydroxide;
[0042] S3: mixing the organic polymer binder coated with aluminum hydroxide and phosphoric acid to obtain the organic polymer binder coated with the phosphate inorganic binder.
[0043] Specifically, in step S1, nonionic surfactant is a key emulsifier, which promotes the formation of uniform and fine emulsion particles by reducing the oil-water interfacial tension, thereby obtaining an emulsion system with good mechanical stability and storage stability. The solution of organic polymer binder refers to an aqueous emulsion containing organic polymer binder, a system with organic polymer binder as solute and water as solvent. The organic polymer binder provided by the present invention is formed by emulsion polymerization, and in the process of emulsion polymerization, the solvent is selected as water. There are mainly a large number of oxyethylene structures in the nonionic surfactant molecules, which can provide hydrogen bonding, and contain a large number of hydroxyl groups that can produce ligands with metal ions. Therefore, by adding nonionic surfactants to the aqueous emulsion of organic polymer binder, a bridge can be provided for the subsequent loading of aluminum source on the surface of organic polymer binder, so that the aluminum source is loaded on the surface of organic polymer binder by hydrogen bonding, and the introduction of aluminum source is realized.
[0044] Specifically, in step S2, an aluminum source is added and dried to obtain an organic polymer binder coated with aluminum hydroxide. The aluminum source generates aluminum hydroxide through a hydrolysis reaction, and then is loaded on the surface of the organic polymer binder through hydrogen bonding to obtain an organic polymer binder coated with aluminum hydroxide.
[0045] Specifically, in step S3, phosphoric acid is added to react with aluminum hydroxide on the surface of the organic polymer binder to generate phosphate inorganic matter.
[0046] In some embodiments, after phosphoric acid is added to react, the reaction product is filtered and washed to improve the purity of the product.
[0047] In some embodiments, in step S3, after obtaining the organic polymer binder coated with the phosphate inorganic binder, the coating layer is further subjected to heat treatment. The heat treatment can improve the crystallinity and adhesion of the coating layer, while ensuring the completion of the chemical reaction and the stability of the material properties.
[0048] Compared with the prior art, the preparation method of the binder provided in the present application is simple, easy to operate, has low energy consumption, and is easy to mass produce.
[0049] In some embodiments, step S1 further includes adding alkanes, fatty alcohols and deionized water to the mixed emulsion.
[0050] Specifically, alkanes are mainly used as solvents to help dissolve monomers and reduce the viscosity between polymer particles, thereby improving the efficiency of the polymerization reaction and the dispersibility of the polymer. Fatty alcohols are usually used as co-emulsifiers to enhance the stability of the emulsion and improve its compatibility in the application medium by adjusting the surface properties of the polymer particles. Deionized water is used as a continuous phase to evenly disperse the monomers or other water-soluble components to form a stable emulsion system.
[0051] In some embodiments, the weight ratio of alkane, fatty alcohol, nonionic surfactant and deionized water is (7-11):1:1:(10-30).
[0052] Specifically, the weight ratio of alkane, fatty alcohol, nonionic surfactant and deionized water can be, but is not limited to, (7:1:1:10), (8:1:1:12), (9:1:1:15), (10:1:1:20), (11:1:1:30). When the weight ratio of alkane, fatty alcohol, nonionic surfactant and deionized water is within this range, the synergistic effect can be better exerted to maintain the stability of the system.
[0053] Mixing the solution containing the organic polymer binder with the mixed solution formed by alkane, fatty alcohol, nonionic surfactant and deionized water can provide a better environment for the introduction of the aluminum source.
[0054] In some embodiments, the alkane includes an alkane having 5 to 10 carbon atoms; and / or the fatty alcohol includes a fatty alcohol having 5 to 10 carbon atoms.
[0055] In some embodiments, the nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether AEO-9, fatty alcohol polyoxyethylene ether AEO-7, fatty alcohol polyoxyethylene ether AEO-15, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer P123, linear secondary alcohol polyoxyethylene ether Tergitol 15-S-9, fatty alcohol polyoxyethylene ether Genapol X-080 and nonylphenol polyoxyethylene ether TX-10.
[0056] Specifically, the carbon number of 5 to 10 may be, but is not limited to, 5, 6, 7, 8, 9, and 10. Alkanes with 5 to 10 carbon atoms include straight-chain alkanes with 5 to 10 carbon atoms and branched-chain alkanes with 5 to 10 carbon atoms; fatty alcohols with 5 to 10 carbon atoms include straight-chain fatty alcohols with 5 to 10 carbon atoms and branched-chain fatty alcohols with 5 to 10 carbon atoms. In fatty alcohol polyoxyethylene ether AEO-9, fatty alcohol polyoxyethylene ether AEO-7, and fatty alcohol polyoxyethylene ether AEO-15, 9, 7, and 15 represent the average number of ethylene oxide units in fatty alcohol polyoxyethylene ether. In some preferred embodiments, alkanes include at least one of n-octane, n-pentane, n-hexane, n-heptane, 2-methylpentane, 3-methylhexane, cyclopentane, cyclohexane, and isooctane, and fatty alcohols include ethanol, n-octanol, and n-butanol. When the alkanes, fatty alcohols and nonionic surfactants are selected within the above ranges, an emulsion system with good mechanical stability and storage stability can be obtained.
[0057] In some embodiments, the aluminum source includes at least one of sodium metaaluminate, aluminum isopropoxide, and aluminum nitrate.
[0058] Specifically, aluminum hydroxide is obtained by hydrolysis of an aluminum source, and then supported on organic polymer binder particles by hydrogen bonding.
[0059] The specific reactions are as follows:
[0060] When the aluminum source is selected from sodium aluminate, the reaction equation is: NaAlO2+HCl+H2O→Al(OH)3↓+NaCl;
[0061] When the aluminum source is selected from aluminum isopropoxide, the reaction equation is: Al(OPri)3+3H2O→Al(OH)3↓+3PriOH;
[0062] When the aluminum source is selected from aluminum nitrate, the reaction equation is: Al(NO3)3+3H2O→Al(OH)3↓+3HNO3.
[0063] In some embodiments, an organic polymer binder coated with aluminum hydroxide is obtained in step S2; in step S3, phosphoric acid and aluminum hydroxide react to generate aluminum dihydrogen phosphate and water, thereby obtaining an organic polymer binder coated with aluminum dihydrogen phosphate. The chemical reaction equation is as follows: Al(OH)3+3H3PO4→Al(H2PO4)3+6H2O; when aluminum hydroxide is excessive, monohydroxy aluminum dihydrogen phosphate is formed, and due to the instability of monohydroxy aluminum dihydrogen phosphate, it will continue to react to form polymerized aluminum phosphate, thereby obtaining an organic polymer binder coated with aluminum phosphate. Therefore, the coating layer can be regulated according to the stoichiometric ratio in the chemical equation.
[0064] In some embodiments, in step S2, an aluminum source is added to the mixed emulsion and stirred for reaction. Specifically, the reaction time is not limited and can be 3 hours to 5 hours.
[0065] In some embodiments, in step S2, after adding the aluminum source to the mixed emulsion for reaction, the reactants are further washed with anhydrous ethanol to remove impurities and unreacted aluminum source to ensure the purity of the reactants. Specifically, the time and number of washing are not limited and can be 2 to 5 times.
[0066] In some embodiments, the weight ratio of the mixed emulsion to the aluminum source is 1:(0.1-1.1).
[0067] Specifically, the weight ratio of the mixed emulsion to the aluminum source can be, but is not limited to, (1:0.1), (1:0.2), (1:0.3), (1:0.4), (1:0.5), (1:0.6), (1:0.7), (1:0.8), (1:0.9), (1:1.0), (1:1.1). When the weight ratio of the mixed emulsion to the aluminum source is within this range, the aluminum source can be better loaded onto the surface of the emulsion polymer binder particles through coordination, and as much aluminum hydroxide-coated organic polymer binder as possible can be generated under the premise of saving resources.
[0068] In some embodiments, the weight ratio of the organic polymer binder coated with aluminum hydroxide to phosphoric acid is 1:(2-4).
[0069] Specifically, the weight ratio of the organic polymer binder coated with aluminum hydroxide to phosphoric acid can be, but is not limited to, 1:2, 1:2.5, 1:3, 1:3.5, 1:4. Within this range, the corresponding coating layer can be formed.
[0070] In some embodiments, in step S3, the organic polymer binder coated with aluminum hydroxide and phosphoric acid are mixed and reacted for 0.5 h to 3 h and at a temperature of 100° C. to 120° C. Within this time and range, the two can react better to generate an organic polymer binder coated with a phosphate inorganic binder.
[0071] In some embodiments, in step S3, the organic polymer binder coated with aluminum hydroxide reacts with phosphoric acid in deionized water. Adding deionized water can evenly disperse the phosphoric acid and the organic polymer binder coated with aluminum hydroxide to form a stable reaction environment.
[0072] In some embodiments, in step S3, after the organic polymer binder coated with aluminum hydroxide and phosphoric acid are mixed and reacted, the reactants are further ground into a suitable particle size, so as to better play a bonding role without affecting the battery performance.
[0073] In a third aspect, the present application provides a diaphragm, comprising a base film and a coating arranged on at least one surface of the base film, the coating comprising the adhesive described in the first aspect above, or an adhesive prepared by the preparation method of the adhesive described in the second aspect above.
[0074] In some embodiments, the coating further comprises ceramic particles, and the weight ratio of the binder to the ceramic particles is (0.3-1): (99-99.7).
[0075] Specifically, the weight ratio of the binder to the ceramic particles can be, but is not limited to, 0.3:99, 0.4:99.1, 0.5:99.2, 0.6:99.3, 0.7:99.4, 0.8:99.5, 0.9:99.6, and 1:99.7. When the weight ratio of the binder to the ceramic particles is within this range, the amount of organic polymer binder used can be reduced while improving the safety performance and charge and discharge performance of the diaphragm, which is beneficial to reducing the impedance of the diaphragm and improving the power performance of the battery.
[0076] In some embodiments, the average particle size of the ceramic particles is 100 nm to 500 nm; and / or the ceramic particles include one or more of boehmite, alumina, barium titanate, zirconium oxide, and magnesium hydroxide.
[0077] Specifically, the average particle size of the ceramic particles may be, but is not limited to, 100 nm, 200 nm, 300 nm, 400 nm, or 500 nm. The ceramic particles include one or more of boehmite, alumina, barium titanate, zirconium oxide, and magnesium hydroxide.
[0078] In some embodiments, the coating further includes a wetting agent.
[0079] Specifically, the wettability of the coating slurry to the base film can be improved according to the actual production line requirements, so that the coating slurry can be completely spread on the surface of the base film, increasing the bonding points between the adhesive and the base film to enhance the bonding stability of the coating while improving the uniformity of the coating.
[0080] In some embodiments, the coating has a thickness of 0.3 μm to 3 μm; and / or the coating has an air permeability per unit thickness of less than 30 s 100 cc. -1 μm -1 .
[0081] Specifically, the thickness of the coating may be, but is not limited to, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2 μm, 2.5 μm, or 3 μm. The air permeability per unit thickness of the coating may be, but is not limited to, less than 30 s 100 cc. -1 μm -1 、20s100cc -1 μm -1 、15s 100cc -1 μm -1 、10s 100cc -1 μm -1 、5s100cc -1 μm -1 .
[0082] In a fourth aspect, the present application provides a battery, comprising the separator described in the third aspect.
[0083] The battery can be a lithium ion battery, a sodium ion battery, etc. The battery includes the above-mentioned separator and has excellent performance.
[0084] In a fifth aspect, the present application provides an electrical device, comprising the battery described in the fourth aspect above.
[0085] Electrical equipment includes, but is not limited to, mobile phones, laptops, tablet computers, cameras, televisions, radios, wearable devices (such as smart watches, smart bracelets, head-mounted stereo headphones, Bluetooth headphones), backup power supplies, new energy vehicles, power tools, large household batteries, etc. Since the electrical equipment uses the above batteries, the performance of the electrical equipment is improved.
[0086] The present invention is further described in detail below by way of examples.
[0087] Example 1
[0088] This embodiment is used to illustrate the binder and preparation method thereof, the separator, and the battery disclosed in the present invention, and includes the following steps:
[0089] (1) Preparation of binder:
[0090] ① Mix 356 g of alkane (specifically n-octane), 35.6 g of fatty alcohol (specifically n-octanol), 35.6 g of nonionic surfactant (specifically fatty alcohol polyoxyethylene ether AEO-9) and 712 g of deionized water to obtain a transparent mixed liquid, and add the transparent mixed liquid to an aqueous emulsion containing polyvinylidene fluoride-hexafluoropropylene copolymer to obtain a mixed emulsion.
[0091] ② Add 276 g of sodium aluminate to 828 g of the mixed emulsion, stir for 4 h, and then perform rotary evaporation. Wash with anhydrous ethanol for 3 times, and vacuum dry at 80° C. to constant weight to obtain aluminum hydroxide-coated polyvinylidene fluoride-hexafluoropropylene copolymer.
[0092] ③ Add 95.25 g of aluminum hydroxide-coated polyvinylidene fluoride-hexafluoropropylene copolymer and 381 g of phosphoric acid into 1000 g of deionized water, stir, react for 2 h, and grind to constant weight at 110° C. to obtain a polyvinylidene fluoride-hexafluoropropylene copolymer binder coated with aluminum dihydrogen phosphate.
[0093] (2) Preparation of diaphragm:
[0094] 49.5 g of aluminum oxide (average particle size of 300 nm) and 0.5 g of the above-prepared binder were dispersed in 200 g of deionized water, stirred for 1 h to obtain a ceramic slurry, and the ceramic slurry was coated on one side of a PE film with a coating thickness of 2 μm, and dried to obtain a diaphragm.
[0095] Example 2
[0096] The difference between Example 2 and Example 1 is that the preparation of the binder is different, as follows, and the rest is the same as Example 1.
[0097] (1) Preparation of binder:
[0098] ③ Add 190.5 g of aluminum hydroxide-coated polyvinylidene fluoride-hexafluoropropylene copolymer and 381 g of phosphoric acid into 1000 g of deionized water, stir, react for 2 h, and grind to constant weight at 110° C. to obtain an aluminum phosphate-coated polyvinylidene fluoride-hexafluoropropylene copolymer binder.
[0099] Example 3
[0100] The difference between Example 3 and Example 1 is that the preparation of the diaphragm is different, as follows, and the rest is the same as Example 1.
[0101] (2) Preparation of diaphragm
[0102] 49.85 g of aluminum oxide (average particle size of 300 nm) and 0.15 g of the above-prepared binder were dispersed in 200 g of deionized water, stirred for 1 hour to obtain ceramic slurry, and the ceramic slurry was coated on one side of a PE film with a coating thickness of 2 μm, and dried to obtain a diaphragm.
[0103] Example 4
[0104] The difference between Example 4 and Example 1 is that the preparation of the binder is different, as follows, and the rest is the same as Example 1.
[0105] (1) Preparation of binder:
[0106] ② Add 276 g of aluminum nitrate to 828 g of the mixed emulsion, stir for 4 h, and then perform rotary evaporation. Wash with anhydrous ethanol for 3 times, and vacuum dry at 80° C. to constant weight to obtain aluminum hydroxide-coated polyvinylidene fluoride-hexafluoropropylene copolymer.
[0107] Example 5
[0108] The difference between Example 5 and Example 2 is that the preparation of the binder is different, as follows, and the rest is the same as Example 2.
[0109] (1) Preparation of binder:
[0110] ② Add 276 g of aluminum nitrate to 828 g of the mixed emulsion, stir for 4 h, and then perform rotary evaporation. Wash with anhydrous ethanol for 3 times, and vacuum dry at 80° C. to constant weight to obtain aluminum hydroxide-coated polyvinylidene fluoride-hexafluoropropylene copolymer.
[0111] Example 6
[0112] The difference between Example 6 and Example 1 is that the preparation of the binder is different, as follows, and the rest is the same as Example 1.
[0113] (1) Preparation of binder:
[0114] ① Mix 356 g of alkane (specifically n-octane), 35.6 g of fatty alcohol (specifically n-octanol), 35.6 g of nonionic surfactant (specifically fatty alcohol polyoxyethylene ether AEO-9) and 712 g of deionized water to obtain a transparent mixed liquid, and add the transparent mixed liquid to an aqueous emulsion containing polyvinylidene fluoride to obtain a mixed emulsion.
[0115] ② Add 276 g of sodium aluminate to the above 828 g of the mixed emulsion, stir for 4 h, and then perform rotary evaporation. Wash with anhydrous ethanol for 3 times, and vacuum dry at 80° C. to constant weight to obtain aluminum hydroxide-coated polyvinylidene fluoride.
[0116] ③ Add 95.25 g of aluminum hydroxide-coated polyvinylidene fluoride and 381 g of phosphoric acid into 1000 g of deionized water, stir, react for 2 h, and grind to constant weight at 110° C. to obtain a polyvinylidene fluoride binder coated with aluminum dihydrogen phosphate.
[0117] Comparative Example 1
[0118] The difference between Comparative Example 1 and Example 1 is that the preparation of the diaphragm is different, as follows, and the rest is the same as Example 1.
[0119] (1) Preparation of diaphragm:
[0120] 49.5 g of aluminum oxide and 0.5 g of aluminum dihydrogen phosphate were dispersed in 200 g of deionized water, and stirred for 1 hour to obtain a ceramic slurry. The ceramic slurry was coated on one side of a PE film, and dried to obtain a diaphragm.
[0121] Comparative Example 2
[0122] The difference between Comparative Example 2 and Comparative Example 1 is that the preparation of the diaphragm is different, as follows, and the rest is the same as Comparative Example 1.
[0123] (1) Preparation of diaphragm:
[0124] 49.5 g of aluminum oxide and 0.5 g of polyvinyl alcohol were dispersed in 200 g of deionized water, and stirred for 1 hour to obtain a ceramic slurry. The ceramic slurry was coated on one side of a PE film, and dried to obtain a diaphragm.
[0125] Comparative Example 3
[0126] The difference between Comparative Example 3 and Comparative Example 1 is that the preparation of the diaphragm is different, as follows, and the rest is the same as Comparative Example 1.
[0127] (2) Preparation of diaphragm:
[0128] 49.5 g of aluminum oxide, 0.25 g of polyvinyl alcohol and 0.25 g of aluminum dihydrogen phosphate were dispersed in 200 g of deionized water and stirred for 1 hour to obtain a ceramic slurry. The ceramic slurry was coated on one side of a PE film and dried to obtain a diaphragm.
[0129] Test Method
[0130] Thermal shrinkage rate: Take the diaphragms prepared in the above embodiments and comparative examples, mark a rectangle with a length and width of 80 mm on the diaphragm, wrap it with two A4 papers, put it in an oven at 120°C for 60 minutes, then take it out, measure the length of the rectangle after shrinkage, and calculate the thermal shrinkage rate MD in the longitudinal direction and the thermal shrinkage rate TD in the transverse direction.
[0131] Membrane coating air permeability: Use a permeability meter to test, first measure the air permeability of the uncoated base membrane, then measure the air permeability of the coated membrane, and the difference between the two is the coating permeability.
[0132] Powder loss: Take the diaphragms prepared in the above embodiments and comparative examples, unwind them and stretch them onto the laminate before lamination, and observe the powder loss of the diaphragm coating with the naked eye.
[0133] Table 1 Test results of membrane performance prepared in various embodiments and comparative examples
[0134] 120℃ MD thermal shrinkage (%) 120℃TD heat shrinkage (%) Coating air permeability Whether to lose fans Example 1 3.55 1.56 15 no Example 2 3.60 1.57 15 no Example 3 3.20 1.32 13 Slight powder loss Example 4 3.53 1.56 15 no Example 5 3.58 1.60 15 no Example 6 3.54 1.39 15 no Comparative Example 1 2.98 0.96 12 Obvious powder loss Comparative Example 2 5.25 2.39 30 no Comparative Example 3 4.01 1.98 15 no
[0135] Under the premise of ensuring that the membrane coating does not fall off, the MD direction heat shrinkage rate, TD direction heat shrinkage rate and air permeability value of the coating at 120°C are key indicators for measuring the performance of the membrane. The lower these values are, the better the performance of the membrane. In Comparative Example 1, the coating using only aluminum dihydrogen phosphate as an inorganic binder exhibits a lower air permeability value, which means that the membrane has a lower gas impedance. However, due to the greater brittleness of the inorganic binder, the coating is prone to powdering. In Comparative Example 2, PVA is used entirely as a binder. Although it has higher adhesion, it also causes the coating to have a high impedance defect. In Comparative Example 3, aluminum dihydrogen phosphate is used as an inorganic binder and PVA is used as an organic binder and simply mixed. Compared with the organic binder coated with the inorganic binder provided in the present application, the diaphragm has a higher thermal shrinkage rate. Since the inorganic structure has a higher thermal stability, the coating structure can maintain the performance of the binder at high temperatures and reduce the degradation of the binder due to thermal decomposition. In addition, the thermal expansion coefficient of inorganic materials is usually lower than that of organic materials. The use of a coating structure can provide better thermal expansion control and reduce the volume change of the binder when the temperature changes, thereby reducing the thermal shrinkage rate.
[0136] It can be seen from the results of Example 1, Example 2, Example 4 and Example 5 that changing the aluminum source used in the synthesis process and adjusting the weight ratio of the aluminum hydroxide-coated polymer phosphoric acid can improve the performance of the diaphragm, and the effect on the performance of the final diaphragm is not significant. In addition, the inner core of the composite binder was changed in Example 6, and the effect on the performance of the diaphragm was not obvious. Example 3 shows that reducing the amount of binder can relatively reduce the air permeability of the diaphragm, which indicates that reducing the amount of binder can reduce the blockage of the pores of the diaphragm. The above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A binder, characterized in that: The binder is a core-shell structure, wherein the core of the core-shell structure comprises an organic polymer binder, and the shell of the core-shell structure comprises a phosphate inorganic binder.
2. The adhesive according to claim 1, characterized in that The organic polymer binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-chlorotrifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trifluoroethylene copolymer, and polyvinylidene fluoride-chlorofluoroethylene copolymer; the phosphate inorganic binder includes at least one of aluminum phosphate and aluminum dihydrogen phosphate.
3. The adhesive according to claim 1 or 2, characterized in that: The average particle size of the binder is 0.2 μm to 8 μm.
4. A method for preparing the adhesive according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: adding a nonionic surfactant to a solution containing the organic polymer binder to obtain a mixed emulsion; S2: adding an aluminum source to the mixed emulsion for reaction, and drying to obtain an organic polymer binder coated with aluminum hydroxide; S3: mixing the aluminum hydroxide coated organic polymer binder and phosphoric acid for reaction, and drying to obtain the phosphate inorganic binder coated organic polymer binder.
5. The method for preparing the adhesive according to claim 4, characterized in that: In step S1, the method further includes adding alkanes, fatty alcohols and deionized water to the mixed emulsion.
6. The method for preparing the adhesive according to claim 5, characterized in that: The weight ratio of the alkane, the fatty alcohol, the nonionic surfactant and the deionized water is (7-11):1:1:(10-30).
7. The method for preparing the adhesive according to claim 5 or 6, characterized in that: In step S1, the alkane includes an alkane having 5 to 10 carbon atoms; and / or the fatty alcohol includes a fatty alcohol having 5 to 10 carbon atoms.
8. The method for preparing the binder according to any one of claims 4 to 7, characterized in that: The nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether AEO-9, fatty alcohol polyoxyethylene ether AEO-7, fatty alcohol polyoxyethylene ether AEO-15, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer P123, linear secondary alcohol polyoxyethylene ether Tergitol 15-S-9, fatty alcohol polyoxyethylene ether Genapol X-080 and nonylphenol polyoxyethylene ether TX-10.
9. The method for preparing the adhesive according to claim 7, characterized in that: The alkane includes at least one of n-octane, n-pentane, n-hexane, n-heptane, 2-methylpentane, 3-methylhexane, cyclopentane, cyclohexane and isooctane; and / or the fatty alcohol includes at least one of ethanol, n-octanol and n-butanol.
10. The method for preparing the binder according to any one of claims 4 to 9, characterized in that: The aluminum source includes at least one of sodium metaaluminate, aluminum isopropoxide and aluminum nitrate.
11. The method for preparing the binder according to any one of claims 4 to 10, characterized in that: In step S2, the weight ratio of the mixed emulsion to the aluminum source is 1:(0.1-1.1).
12. The method for preparing the binder according to any one of claims 4 to 11, characterized in that: In step S3, the weight ratio of the organic polymer binder coated with aluminum hydroxide to the phosphoric acid is 1:(2-4).
13. A diaphragm, characterized in that: The invention comprises a base film and a coating arranged on at least one surface of the base film, wherein the coating comprises the adhesive according to any one of claims 1 to 3 or an adhesive prepared by the method for preparing the adhesive according to any one of claims 4 to 12.
14. The diaphragm according to claim 13, characterized in that The coating layer includes ceramic particles, and the weight ratio of the binder to the ceramic particles is (0.3-1): (99-99.7).
15. The diaphragm according to claim 14, characterized in that The average particle size of the ceramic particles is 100 nm to 500 nm; and / or the ceramic particles include one or more of boehmite, aluminum oxide, barium titanate, zirconium oxide, and magnesium hydroxide.
16. The diaphragm according to any one of claims 13 to 15, characterized in that: The coating includes a wetting agent.
17. The diaphragm according to any one of claims 13 to 16, characterized in that: The coating has a thickness of 0.3 μm to 3 μm; and / or the coating has an air permeability per unit thickness of less than 30 s 100 cc -1 μm -1 .
18. A battery, characterized in that: A diaphragm comprising any one of claims 13 to 17.
19. An electrical equipment, characterized in that: Comprising the battery of claim 18.